PENGAPLIKASIAN BIO-INSEKTISIDA Beauveria bassiana DALAM MENEKAN INTENSITAS SERANGAN PADA TANAMAN SAWI (Brassica juncea L.) - Asnita Pasaribu; Akhmad Gazali; Rabiatul Wahdah (Agroekotek View, 2022)
Mustard (Brassica juncea L.) is a vegetable plant that is very easy to cultivate in both cold and hot areas and has many benefits for the body. Beauveria bassiana is one of the entomopathogenic fungi that can be widely used as biological control of plant pests. The purpose of this study was to determine the effect and the best dose in the application of bio-insecticide B. bassiana in suppressing the intensity of attack on mustard plants. This study used a one-factor randomized block design (RAK), which consisted of five treatments and was repeated five times to obtain twenty-five experimental units with 3 samples each, requiring 75 plants. A1 : No treatment (control with water), A2 : 20 (4.5 x 1010) / 500 mL water, A3 : 30 (4.5 x 1010) / 500 mL water, A4 : 40 (4.5 x 1010) / 500 mL water, A5 : 50 (4.5 x 1010) / 500 mL water. Bioinsecticide Beauveria bassiana has an effect on the intensity of pest attack. The best bio-insecticide product containing the active ingredient Beauveria bassiana is A5 : 50 (4.5 x 1010) / 500 mL water.). However, from an economic point of view as well as the concentration of the dose, it is recommended that treatment A3 : 30 (4.5 x 1010) / 500 mL of water be used because the effect is not significantly different from that of treatment A5 : 50 (4.5 x 1010) / 500 mL of water.).